A wicked conceit - Huber, Anna Lee (Huber, Anna Lee. Lady Darby novel., 2021)
"Expectant parents Kiera and Sebastian Gage have been hoping for a respite from their inquiries, but murder and mayhem have a startling way of dropping into their laps in the all-new historical mystery in this national bestselling series. March 1832. Edinburgh, Scotland. Kiera and Gage have been eagerly awaiting their bundle of joy but trouble has been brewing in the form of roguish criminal Bonnie Brock Kincaid. A new book and subsequent play features some of Kincaid's daring exploits as well as thinly veiled representations of Kiera and Gage. Rumors are swirling that Bonnie Brock, not Gage, is the father of Kiera's unborn child. Once again Kiera finds herself fighting off scandalous lies while the play's popularity continues to grow. A rash of crimes break out across the city, seemingly inspired by the play and book. When the publisher is found brutally murdered-in an imitation of a gruesome scene-the finger not only points to Bonnie Brock as the possible culprit, but also the Gages, who have been outspoken in their condemnation of the tale. Now, the Gages are on a hunt to unmask a deadly fiend. But family quarrels and the revelation of a secret Kiera has been keeping from Sebastian threaten to undermine their investigation. When they find themselves in the crosshairs of the killer, they will soon discover that the truth does not always set you free, and death can lurk around any corner"--